SYNTHESIS OF NEW PYRIMIDINE DERIVATIVES AND EVALUATION OF THEIR ANTICANCER AND ANTIMICROBIAL ACTIVITIES - ALL, EATEDAL H. ABD EL; Osman, Nermine A; El-mahmoudy, Amany M; Hassan, Alaa N (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The objective of this work is to synthesize new pyrimidine derivatives starting from ethyl 2,4-dioxo-4-(thiophen-2-yl)butanoate. Several oxadiazole, triazole, and thiadiazole moieties were incorporated into the pyrimidine backbone. The structure of the novel compounds was characterized by elemental analysis and spectroscopic methods. Methods: Synthesis of the target compounds was materialized starting from 2-oxo-6-(thiophen-2-yl)-2,3-dihydropyrimidine-4-carbohydrazide (4) which was prepared from the appropriate ethyl 2-oxo-6-(thiophen-2-yl)-2,3 dihydropyrimidine-4-carboxylate (2). Several synthetic pathways were used for the preparation of the targets. Some of the newly synthesized compounds were subjected to in vitro cytotoxic screening against breast carcinoma and colon carcinoma cell lines. On the other hand, the antimicrobial activity evaluation of some newly prepared compounds was performed using cup plate diffusion method. Results: It was observed that the oxadiazole derivative 7b was the most potent compound against breast carcinoma cell line (IC =7.6 Î¼g/ml). However, pyrimidine carrying substituted 1,2,4-triazole-2-thione moiety at position 6, 11 showed the highest cytotoxic activity against colon carcinoma cell line (IC 50 =4.7 Î¼g/ml). On the other hand, compound 5c was the most active broad spectrum antimicrobial agent against the chosen microbial strains. Conclusion: From the observed results, further investigations recommended for the synthesis of heterocycles incorporated to pyrimidine backbone as cytotoxic as well as broad spectrum antimicrobial agents. Keywords: Pyrimidine, Oxadiazole, Triazole, Thiadiazole, In vitro anticancer study, Antimicrobial study. 50